Melatonin as a Mediator of the Gut Microbiota-Host Interaction: Implications for Health and Disease - María-Ángeles B; Maria-Angeles Rol (MDPI AG, 2023)
In recent years, the role played by melatonin on the gut microbiota has gained increasingly greater attention. Additionally, the gut microbiota has been proposed as an alternative source of melatonin, suggesting that this antioxidant indoleamine could act as a sort of messenger between the gut microbiota and the host. This review analyses the available scientific literature about possible mechanisms involved in this mediating role, highlighting its antioxidant effects and influence on this interaction. In addition, we also review the available knowledge on the effects of melatonin on gut microbiota composition, as well as its ability to alleviate dysbiosis related to sleep deprivation or chronodisruptive conditions. The melatonin-gut microbiota relationship has also been discussed in terms of its role in the development of different disorders, from inflammatory or metabolic disorders to psychiatric and neurological conditions, also considering oxidative stress and the reactive oxygen species-scavenging properties of melatonin as the main factors mediating this relationship.